Lessons Learned from the Design and Implementation of the Tuberculosis Free Nepal Initiative - Prajowl Shrestha; Gokul Mishra; Mukti Nath Khanal; Naveen Prakash Shah; Deepak Dahal; Barsha Thapa; Lok Raj Joshi; Namita Ghimire; Tom Wingfield (Journal of Nepal Medical Association)
Introduction: Nepal has a persistently high burden of tuberculosis. Despite implementation of multiple interventions by the National tuberculosis Program, Nepal is not on track to achieve many of WHO’s End tuberculosis Strategy targets.